2006
DOI: 10.1038/sj.ki.5000446
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sudden death in hemodialysis patients

Abstract: Hemodialysis (HD) is an intermittent procedure during which large fluid and electrolyte shifts occur. We hypothesized that sudden death occurrences in HD patients are related to the timing of HD, and that they occur more frequently in the 12 h period starting with dialysis and in the 12 h period at the end of the dialysis-free weekend interval. In a retrospective study, 228 patient deaths were screened to determine if they met the criteria for sudden death. Information was obtained from clinic charts, dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
305
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(328 citation statements)
references
References 31 publications
12
305
1
10
Order By: Relevance
“…Bleyer et al (32) observed that sudden death is particularly frequent hours after the start of dialysis on the one hand and during the hours preceding the next dialysis session on the other hand. Furthermore, sudden death is particularly frequent after the long weekend (33,34).…”
Section: Electrolyte Shifts and Hypervolemia Related To Dialysis Sessmentioning
confidence: 99%
“…Bleyer et al (32) observed that sudden death is particularly frequent hours after the start of dialysis on the one hand and during the hours preceding the next dialysis session on the other hand. Furthermore, sudden death is particularly frequent after the long weekend (33,34).…”
Section: Electrolyte Shifts and Hypervolemia Related To Dialysis Sessmentioning
confidence: 99%
“…Several studies have identified risk factors for SCD in HD patients, but few have compared predictors for SCD with other causes of death (2)(3)(4)(5)(6)(7)(8). The latter is important given that treatment recommendations may vary depending on the risk factor profile of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The US Renal Data System (USRDS) report attributes the single largest specific cause of death from cardiovascular disease to arrhythmias or cardiac arrest (1). Although certain risk factors associated with sudden cardiac death (SCD) in HD patients are similar to those in the general population, factors unique to kidney failure and the HD procedure play a prominent role but remain poorly understood (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…However, sudden death and cardiac events are the most significant cause of mortality in the dialysis population. The increased risk of sudden death occurs at the end of the weekend interval immediately before dialysis or within 12 hours of the start of a dialysis session (6). Although the dialysate calcium concentration is unlikely to be a risk factor for deaths occurring at the end of the weekend interval, it could very well contribute to the large number of deaths and cardiac events occurring in the hours after the dialysis session.…”
mentioning
confidence: 99%
“…Although the dialysate calcium concentration is unlikely to be a risk factor for deaths occurring at the end of the weekend interval, it could very well contribute to the large number of deaths and cardiac events occurring in the hours after the dialysis session. In a study from our center, approximately one-third of all sudden deaths occurred within 12 hours of the start of the dialysis treatment (6).…”
mentioning
confidence: 99%